Subwersja, nie sztuka. Korzenie, założenia i problemy fan studies - Urbańczyk, Agnieszka (Przestrzenie Teorii, 2019)
Though the area of fan studies has been a prolific field of research for almost three decades, it is still marginal in Poland. The purpose of this paper is not to present types of fan activity, but to discuss the way they are researched and how this research was influenced by ethnography, Pierre Bourdieu’s Critical Theory and cultural studies (especially reception studies). The classic works of fan studies have established a still dominant paradigm of the political and subversive character of fan activity, which is followed by a notion of fandom as a heterotopia. In order to continue the research, it has been necessary for academics to establish a position of involvement instead of distance and to create ethical guidelines preventing fans from being colonized as the Other. However, that may cause petrification of fan studies.